CREATIVE ATMOSPHERE AS AN IMPORTANT WAREHOUSE CREATIVE TEACHER TRAINING - Grybenko, H.Ye. (Pedagogy of Higher and Secondary Education, 2003)
The article analyses different approaches to definition of teacher’s creative personality. The problem of making creative atmosphere of high school study process as an important factor of teachers creative personality formation is investigated.